Lactation Support and Breastfeeding Duration in Jaundiced Infants: A Randomized Controlled Trial - Pound, Catherine M. (PLoS One, 2015)
OBJECTIVES: Neonatal jaundice is the most common problem in full-term infants during the immediate post-natal period. We examined the effect of a lactation support intervention on breastfeeding duration in hospitalized jaundiced infants. STUDY DESIGN: We conducted a randomized controlled trial with a qualitative component involving mothers of hospitalized jaundiced breastfed infants <4 weeks of age. Mothers receiving the intervention met with an International Board-Certified Lactation Consultant in hospital and 1–3 times post discharge. Both groups received the standard care for jaundice. The primary outcome was exclusive breastfeeding at 3 months. To the exception of research assistants enrolling participants and completing qualitative interviews, all research staff, investigators and statisticians were blinded to group assignment. Qualitative interviews elicited feedback on breastfeeding experiences for both groups. RESULTS: 99 participants were recruited, and 86 analyzed for primary outcome. There was no difference in exclusive breastfeeding at 3 months between groups (RR 0.84, 95% CI 0.56–1.24, p = 0.40) or in the secondary outcomes. 31 participants were included in the qualitative analysis. Participants in the intervention group described an increase in comfort and confidence levels with breastfeeding. Participants in the control group reported limited lactation support. CONCLUSIONS: Our hospital-based lactation support program did not result in a higher proportion of mothers exclusively breastfeeding at 3 months compared to current hospital standard care. Qualitative feedback from the intervention group suggests that mothers’ confidence was increased, which is linked to breastfeeding duration. The decision to breastfeed is multifactorial and hospital-based lactation support may be only a small piece of the puzzle in hospitalized jaundiced infants. Further studies may be needed to fully elucidate the impact of an in-hospital lactation support program on successful breastfeeding for these infants. TRIAL REGISTRATION: ClinicalTrials.gov NCT00966719 https://www.clinicaltrials.gov/ct2/show/NCT00966719?term=Lactation+Support+and+Breastfeeding+Duration+in+Jaundiced+Infants%3A+a+Randomized+Controlled+Trial&rank=1